An improved algorithm with Multifactor Authentication Scheme for Telecare Medical Information System (TMIS) - Kumar Nayek, Asit; Krishna Jana, Radha; Adhikary, Arpan (International Journal of Computer Sciences and Engineering, 2026)
Telemedicine and its base, Telecare Medical Information System (TMIS), are becoming popular trend in the post COVID days. Faster Internet services and wireless technologies essentially provide faster data transfer facilities in Internet of Things (IoT) environment. To provide remote healthcare services, wearable and household medical devices are connected to form IoT networks. Thus, private data are exposed over the Internet and privacy maintenance is an issue. Elliptic Curve Cryptographic (ECC), a public key system, may be used since it can handle lightweight keys for small devices. One way hash- functions are very useful to protect any data but are irreversible. Hashing is useful to implement for data integrity. Our proposed system will use public key cryptosystem where keys are generated in ECC over a cyclic field. Beside this, One Time Password (OTP) will be used to provide another layer of user verification that will be transmitted in the GSM like telephone network. We will expect to provide security at different levels for all kind of users in a TMIS environment.